Analysis of the quality of life in patients with multiple sclerosis within 3 years after high-dose immunosuppressive therapy with autologous hematopoietic stem cell transplantation - A. Yu. Polushin; E. I. Lopatina; A. A. Tsynchenko; Yu. R. Zalyalov; I. B. Skiba; T. P. Nikitina; N. M. Porfirieva; T. I. Ionova; N. A. Totolyan; A. D. Kulagin (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. To date, data have been accumulated indicating the high effectiveness of the HDIT-AHSCT and the possibility of preserving and improving the quality of life of patients after its application.The objective was to analyze the dynamics of quality of life using standardized assessment tools in patients with MS for 3 years after the use of HDIT-AHSCT, who participated in the program of clinical approbation of the method.Methods and materials. The single-center observational study included 21 patients (10 women, 11 men) with a reliable diagnosis of MS, who underwent HDIT-AHSCT at the Pavlov First Saint Petersburg State Medical Universityin accordance with the protocol of clinical approbation. Distribution by type of MS course: remitting (RMS) 16 (76.2 %), secondary progressive (SPMS) 4 (19 %), primary progressive (PPMS) 1 patient (4.8 %). The assessment of quality of life (SF-36, FAMS, CSP-MS42, HADS) and severity of disability (EDSS) in all patients was performed before, 12 and 36 months after HDIT-AHSCT.Results. Three years after the HDIT-AHSCT, a significant decrease in weakness, feelings of constant fatigue and rapid fatigue during exertion was recorded. The level of anxiety decreased in more than 50 % of patients. A direct relationship between the dynamics of clinical characteristics and the data of the scales of the SF-36 questionnaire was revealed; at the same time, after 36 months, an improvement in all parameters of the scale was noted.Conclusion. The assessment of the indicators of the quality of life questionnaires allows us to confirm the effectiveness and significance of therapy not only from the point of view of objective clinical and radiation parameters necessary for the evidence base of the treatment method, but also from the patient’s position, which in conditions of a chronic progressive process is an integral factor for the appointment of therapeutic intervention.